2019
DOI: 10.1038/s41591-019-0525-0
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping exclusive breastfeeding in Africa between 2000 and 2017

Abstract: Exclusive breastfeeding (EBF)—giving infants only breast-milk (and medications, oral rehydration salts and vitamins as needed) with no additional food or drink for their first six months of life—is one of the most effective strategies for preventing child mortality1–4. Despite these advantages, only 37% of infants under 6 months of age in Africa were exclusively breastfed in 20175, and the practice of EBF varies by population. Here, we present a fine-scale geospatial analysis of EBF prevalence and trends in 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 41 publications
3
79
0
Order By: Relevance
“…To improve global breastfeeding rates, the World Health Organisation endorsed a set of Global Nutrition Targets (WHO GNT, including Goal-5), which aims to increase the global EBF rate to at least 50% by the year 2025 [11]. However, a recent study indicated that only three African countries (Guinea-Bissau, Rwanda, and São Tomé and Príncipe) are on track to meet the GNT for EBF [12].…”
Section: Introductionmentioning
confidence: 99%
“…To improve global breastfeeding rates, the World Health Organisation endorsed a set of Global Nutrition Targets (WHO GNT, including Goal-5), which aims to increase the global EBF rate to at least 50% by the year 2025 [11]. However, a recent study indicated that only three African countries (Guinea-Bissau, Rwanda, and São Tomé and Príncipe) are on track to meet the GNT for EBF [12].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of measurement, advances in methods such as spatial statistics have allowed highly accurate sub-regional mapping of population characteristics in global health research. For example, one method estimates the resolution of 5 km by 5 km cells for the African continent, HIV prevalence [16] and exclusive breastfeeding until 6 months of age [17]. In another study, the authors created similar high-resolution estimates of educational attainment across low and middle-income countries [18].…”
Section: Precision Public Healthmentioning
confidence: 99%
“…Studies were included if they meet the following criteria: (i) experimental or quasi-experimental study design (including randomized controlled trials [RCT], non-RCTs, before and after studies, and interrupted time-series studies) with or without comparison groups or cluster; (ii) conducted among pregnant women and mothers living with live children under 2 years to improve IYCF practices; (iii) used any type of IYCF interventions delivered between the antenatal period and 24 months postpartum; (iv) measured at least one core IYCF indicators such as EIBF, EBF, the introduction of solid, semi-solid and soft foods, continued breastfeeding at one year, MDD, MMF, and minimum acceptable diet (MAD); (v) were published in the English language; and (vi) conducted in Ethiopia from the year 2000 to date. We considered studies published over this period to demonstrate the impacts of the speci c IYCF interventions in the context of Ethiopia to re ect the implementation of relevant global health programs, including the MDGs and the current SDGs [23].…”
Section: Eligibility Criteriamentioning
confidence: 99%